1965
DOI: 10.1099/00221287-38-2-197
|View full text |Cite
|
Sign up to set email alerts
|

The Virulence of Biochemical Variants of Streptococcus pyogenes

Abstract: SUMMARYTwo biochemical variants were obtained from a strain of Streptococcus pyogenes, type 19. One variant, known as 'starch-positive', always produced amylomaltase, readily forming starch from maltose. The other variant, known as 'starch-negative', did not usually form starch from maltose in the same cultural conditions. The starch-positive variant had low mouse virulence and the starch-negative variant had high mouse virulence. The starch positive variant was avirulent for the rat, but the starch-negative v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1969
1969
1969
1969

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In spite of much work in many countries there is little precise information on the factors which render some strains of Staph. aureus apparently more successful than others, Williams (1966) suggests that the success of an epidemic staphylococcus, such as phage-type 80/81, may lie in its superior ability in colonizing the skin, rather than in increased toxin production, Crowley (1965) has studied the virulence of 2 bioehemical variants of Streptococcus pyogenes and has found that in strains possessing satisfactory supplies of M-protein, the presence of an enzyme amylomaltase which converts maltose to stareh, is associated with low mouse-virulence. It is of special interest that these starch-forming strains are not infrequently isolated in association with glomerulo-nephritis and rheumatic fever, FUTURE PROSPECTS Enough has been said to indicate how much there is left to learn about the eutaneous ecosystem.…”
Section: Coactions Of the Normal Floramentioning
confidence: 99%
“…In spite of much work in many countries there is little precise information on the factors which render some strains of Staph. aureus apparently more successful than others, Williams (1966) suggests that the success of an epidemic staphylococcus, such as phage-type 80/81, may lie in its superior ability in colonizing the skin, rather than in increased toxin production, Crowley (1965) has studied the virulence of 2 bioehemical variants of Streptococcus pyogenes and has found that in strains possessing satisfactory supplies of M-protein, the presence of an enzyme amylomaltase which converts maltose to stareh, is associated with low mouse-virulence. It is of special interest that these starch-forming strains are not infrequently isolated in association with glomerulo-nephritis and rheumatic fever, FUTURE PROSPECTS Enough has been said to indicate how much there is left to learn about the eutaneous ecosystem.…”
Section: Coactions Of the Normal Floramentioning
confidence: 99%